Control of blood loss at caesarean section - Sheehan, Sharon Rachel (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Obstetrics and Gynaecology, 2011)
Caesarean section is one of the most commonly performed major operations in women throughout the world. Operative morbidity includes haemorrhage, anaemia, blood transfusion and in severe cases, maternal death. The value of routine oxytocics in the third stage of vaginal birth has been well established and it has been assumed that these benefits apply to caesarean delivery as well. There is very limited evidence to guide practice.
Keywords: Obstetrics and Gynaecology, Ph.D.; Ph.D. Trinity College Dublin